2013
DOI: 10.15376/biores.8.2.2867-2880
|View full text |Cite
|
Sign up to set email alerts
|

Combined Strategies for Improving the Production of Recombinant Rhizopus oryzae Lipase in Pichia pastoris

Abstract: We have developed a yeast Pichia pastoris system for the high-level expression of recombinant Rhizopus oryzae lipase (ROL), which is a potentially effective catalyst in the solvent-free production of biodiesel fuel. In the glycerol fed-batch phase, the combination of the dissolvedoxygen-stat and gradient-control glycerol feeding strategies resulted in a higher cell biomass in the P. pastoris culture, with shorter feed times. In the methanol fed-batch phase, a constant methanol concentration of 0.3-0.5% (v/v) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Heterologous protein expression in shake flask cultures of P. pastoris is usually performed in complex BMGY medium, whose composition, however, is not optimized; therefore, modifications have been proposed (Stratton et al, 1998; Pichia Fermentation Process Guidelines, 2002; Ghosalkar et al, 2008; Li et al, 2013). Even though P. pastoris can grow in a large range of pH (from 3.0 to 7.0) (Ahmad et al, 2014), our previous results (not shown) demonstrated that ASNase II activity did not significantly vary in the pH range 5.0–6.0.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Heterologous protein expression in shake flask cultures of P. pastoris is usually performed in complex BMGY medium, whose composition, however, is not optimized; therefore, modifications have been proposed (Stratton et al, 1998; Pichia Fermentation Process Guidelines, 2002; Ghosalkar et al, 2008; Li et al, 2013). Even though P. pastoris can grow in a large range of pH (from 3.0 to 7.0) (Ahmad et al, 2014), our previous results (not shown) demonstrated that ASNase II activity did not significantly vary in the pH range 5.0–6.0.…”
Section: Resultsmentioning
confidence: 99%
“…High cell density cultures of P. pastoris in bioreactor are usually carried out on chemically-defined high-salt concentration broth consisting of a modified basal salt medium (BSMm) enriched with a Pichia trace metal (PTM) solution (Ferrara et al, 2006; Julien, 2006; Ghosalkar et al, 2008; Li et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…In order to improve rROL production and minimise the proteolysis in Mut S phenotype strain cultures, different operational strategies have been studied. Li et al [143] described that maintaining a constant methanol concentration during the fed-batch cultivation showed a better lipase production than adjusting methanol feeding rate to keep DO over 35% (DO-stat). However, the former strategy needs to be complemented to avoid proteases expression and lipase degradation.…”
Section: Rrol P Aoxmentioning
confidence: 99%
“…Using this yeast provides a number of advantages, including little endogenous protein secretion, the absence of endogenous lipases and esterases, the presence of a powerful, tightly regulated methanol-inducible alcohol oxidase 1 promoter (P AOX1 ), and the ability to grow at high cell densities on defined media [30]. The high suitability of P. pastoris for ROL production is confirmed by the vast amount of literature on its cloning and expression [31][32][33][34][35]. Previous studies have examined the effects of cloning and expressing the whole ROL prosequence (97 amino acids) with the mature sequence in P. pastoris [36,37].…”
Section: Introductionmentioning
confidence: 99%